Human-Robot Interaction: Kinematics and Muscle Activity Inside a Powered Compliant Knee Exoskeleton - Knaepen, Kristel; Beyl, Pieter; Duerinck, Saartje; Hagman, Friso; Lefeber, Dirk; Meeusen, Romain (IEEE transactions on neural systems and rehabilitation engineering, 2014)
Until today it is not entirely clear how humans interact with automated gait rehabilitation devices and how we can, based on that interaction, maximize the effectiveness of these exoskeletons. The goal of this study was to gain knowledge on the human-robot interaction, in terms of kinematics and muscle activity, between a healthy human motor system and a powered knee exoskeleton (i.e., KNEXO). Therefore, temporal and spatial gait parameters, human joint kinematics, exoskeleton kinetics and muscle activity during four different walking trials in 10 healthy male subjects were studied. Healthy subjects can walk with KNEXO in patient-in-charge mode with some slight constraints in kinematics and muscle activity primarily due to inertia of the device. Yet, during robot-in-charge walking the muscular constraints are reversed by adding positive power to the leg swing, compensating in part this inertia. Next to that, KNEXO accurately records and replays the right knee kinematics meaning that subject-specific trajectories can be implemented as a target trajectory during assisted walking. No significant differences in the human response to the interaction with KNEXO in low and high compliant assistance could be pointed out. This is in contradiction with our hypothesis that muscle activity would decrease with increasing assistance. It seems that the differences between the parameter settings of low and high compliant control might not be sufficient to observe clear effects in healthy subjects. Moreover, we should take into account that KNEXO is a unilateral, 1 degree-of-freedom device.